NOWE SPOJRZENIE ŚWIATOWEJ RADY KOŚCIOŁÓW NA MISJE I EWANGELIZACJĘ - Baksik, Estera (Studia Oecumenica, 2013)
The Commission on World Mission and Evangelism of the World Council of Churches worked out a document Together Towards Life: Mission and Evangelism in Changing Landscapes. It is the first document of this type which is devoted entirely to mission and evangelism since 30 years. The document consists of four parts: Spirit of Mission: Breath of Life, Spirit of Liberation: Mission from the Margins, Spirit of Community: Church on the Move, Spirit of Pentecost: Good News for All. While discussing the content of particular parts of the document, the current article referred to the stand of the Roman Catholic Church on mission and evangelism. In many points the stance of the World Council of Churches contained in the document Together Towards Life: Mission and Evangelism in Changing Landscapes and the approach of the Catholic Church (presented on the basis of documents of Ecumenical Councils, encyclicals, apostolic exhortations and papal speeches) seems to be similar.